The Effects of KBT-3022, a New Anti-platelet Agent, on Hemorheological Properties in Guinea Pigs - Yamamoto, Noriko; Yokota, Koichi; Yamashita, Akira; Oda, Minoru (Thrombosis and Haemostasis, 1995)
Using guinea pigs, a study was conducted on the effects of KBT-3022, a new anti-platelet agent, on hemorheological properties in various tests including blood filterability, blood viscosity, shear stress-induced red blood cell (RBC) deformability and contents of ATP and 2,3-diphosphoglycerate (2,3-DPG). Oral administration of KBT-3022 at 1 and 10 mg/kg significantly increased blood filterability, and significantly reduced blood viscosity at 10 mg/kg without changing the hematocrit, plasma fibrinogen concentration or plasma viscosity. KBT-3022 (10 mg/kg, p.o.) improved RBC deformability in response to shear stress, which was evoked by passing the blood through a thin tube. This dose of KBT-3022 also increased the contents of ATP and 2,3-DPG in RBC. These findings indicate that KBT-3022 may reduce blood viscosity as a sequel to improvement of RBC deformability through direct action on RBC. The increase in the intracellular levels of ATP and 2,3-DPG was considered to be involved in this improvement of hemorheological properties. These hemorheological effects of KBT-3022 appear to be promising for the treatment of patients with ischemic vascular disease.